PIROXICAM YANG DIDUGA SEBAGAI AGEN PENYEBAB STEVEN-JOHNSON SYNDROME : SEBUAH LAPORAN KASUS - Rifqie Courie; Dedianto Hidajat (Unram Medical Journal, 2022)
Steven-Johnson Syndrome (SJS) is an acute mucocutaneous reaction characterized by extensive necrosis and exfoliation of the epidermal layer. The most common etiology or trigger in SJS cases is drugs or their metabolites, followed by infection and idiopathic. The most common drugs that trigger SJS include sulfonamides, non-steroidal anti-inflammatory drugs (NSAIDs) such as oxicam derivatives, imidazole antifungals, cephalosporins, anticonvulsants, allopurinol, broad-spectrum bactericidal agents, and the regimen. Highly Active Anti Retroviral Therapy (HAART). A 42-year- old woman with complaints of blisters on the lips and eyelids and red spots on the body, hands and feet. These complaints began to arise after the patient took the drug Piroxicam. The lesions on the forehead, eyelids, lips and neck in the form of erythematous macular-patch lesions, irregular in shape, poorly demarcated, with lenticular-plaque size, discrete-confulnous arrangement, regional distribution accompanied by erosions and hemorrhagic crusts. lesions on the abdomen, hands and feet in the form of macules – erythematous patches with purpura in the central part, round andin shape irregular, with miliary-plaque size, with discrete-confluent arrangement and generalized distribution with blackish brown erosions and crusts on the left upper quadrants of the abdomen, erosions and hemorrhagic crusts on the left upper arm. The patient was diagnosed with Steven- Johnson Syndrome who later died from aspiration on day 9. The presence of precipitating factors and skin and mucosal lesions that lead to SJS can speed up clinical decision making so that treatment is given more quickly.